Analisis Penegakan Hukum terhadap Tindak Pidana Politik Uang dalam Pemilihan Kepala Daerah ditinjau dari Undang-Undang Nomor 10 Tahun 2016 - Parlindungan, Ahmad (Mahesa Research Center, 2019)
Regional Head Elections or abbreviated as (Pilkada), fraudulencies are often occurs as seen in one of the court verdict no. 381 /Pid.Sus/2018.PN,Psp. About money politics. Money politics is a from of giving or promising to bribe someone with the intention so thet the person does not carry out his righs in certain way during the general election. The regional head election is a main momentum of democracy in the implementation of each general election be held every pair of candidates expects no fraudulent acts carried out by the candidate pairs in order to create a conducive regional head general election. Therefor money politic perpetrators can be held accountable for their action as is have been regulated in Law No.10 of 2016 concerning the second amendement to Law No. 1 of 2015 concerning the second amendment to law number 1 of 2014 concerning the election of regional heads, while there are 25 types of criminal acts for the election of regional heads, while there are 5 articles concerning on criminal acts of general election in KUHP. Pilkada violations are divided into there, which are administrative violation, criminal violations of money politics, and disputes over the result of general elections in this case the election of regional heads. Administrative violations were reported to the electoral commission and forwarded to KPUD. Violations of general election criminal proceeds with the criminal justice system (police, public prosecutor, judiciary) in accordance with the criminal procedure code, preceded by report from thev public or candidate pairs to the election supervisory committee no later than seven days after the report is received, while disputer over the resoult of the regional head elections originally handled by the supreme court was handed over to the constitional court.